The role of long noncoding RNAs as regulators of the epithelial–Mesenchymal transition process in oral squamous cell carcinoma cells - Shao, Zifei; Wang, Xiang; Li, Yiyang; Hu, Yanjia; Li, Kun (Frontiers in Molecular Biosciences, 2022)
Oral squamous cell carcinoma (OSCC) is one of the most common cancers, accounting for 3% of all tumors. OSCC is highly migratory and invasive, with a 5-year survival rate of only about 50%. The invasiveness of OSCC mainly depends on epithelial-mesenchymal transformation (EMT), in which epithelial cells transform into mesenchymal cells by losing cell-cell adhesion and polarity. An in-depth understanding of the mechanism of EMT in tumors plays an important role in preventing the migration of cancer cells at an early stage, or in eliminating metastatic tumor cells at a later stage. LncRNAs play an important role in the process of cells from normal phenotype to cancerous phenotype. Recently, many studies have shown the presence of multiple lncRNAs, which are closely related to EMT. In this review, we conducted a comprehensive investigation of the dysregulated lncRNAs in OSCC with particular attention to the function and regulatory mechanisms of several important lncRNAs, and we discussed their roles as OSCC diagnostic and prognostic biomarkers and their potential clinical applications as therapeutic targets.